Sonographic findings in two cases of complicated pregnancy in women previously treated with endometrial ablation. Issue 9 (1st August 2012) - Holt, Roxane; Santiago‐Muñoz, Patricia; Nelson, David B.; Twickler, Diane
<x xml:space="preserve">Abstract</x> When medical therapy fails for menorrhagia in a premenopausal woman, minimally invasive endometrial ablation can be used as a conservative management alternative to hysterectomy. Endometrial ablation alone is not considered effective contraception, and women of reproductive age can become pregnant after ablative therapy. We now present two cases of pregnancy after endometrial ablation and associated imaging where both cases required cesarean hysterectomy due to post partumhemorrhage. Pregnancy after endometrial ablation incurs increased morbidity and diagnostic dilemmas. © 2012 Wiley Periodicals, Inc. J Clin Ultrasound41:566–569, 2013.